Characterization of chemical contaminants generated by a desktop fused deposition modeling 3-dimensional Printer. Issue 7 (3rd July 2017) - Stefaniak, Aleksandr B.; LeBouf, Ryan F.; Yi, Jinghai; Ham, Jason; Nurkewicz, Timothy; Schwegler-Berry, Diane E.; Chen, Bean T.; Wells, J. Raymond; Duling, Matthew G.; Lawrence, Robert B.; Martin, Stephen B.; Johnson, Alyson R.; et al.
ABSTRACT: Printing devices are known to emit chemicals into the indoor atmosphere. Understanding factors that influence release of chemical contaminants from printers is necessary to develop effective exposure assessment and control strategies. In this study, a desktop fused deposition modeling (FDM) 3-dimensional (3-D) printer using acrylonitrile butadiene styrene (ABS) or polylactic acid (PLA) filaments and two monochrome laser printers were evaluated in a 0.5 m 3 chamber. During printing, chamber air was monitored for vapors using a real-time photoionization detector (results expressed as isobutylene equivalents) to measure total volatile organic compound (TVOC) concentrations, evacuated canisters to identify specific VOCs by off-line gas chromatography-mass spectrometry (GC-MS) analysis, and liquid bubblers to identify carbonyl compounds by GC-MS. Airborne particles were collected on filters for off-line analysis using scanning electron microscopy with an energy dispersive x-ray detector to identify elemental constituents. For 3-D printing, TVOC emission rates were influenced by a printer malfunction, filament type, and to a lesser extent, by filament color; however, rates were not influenced by the number of printer nozzles used or the manufacturer's provided cover. TVOC emission rates were significantly lower for the 3-D printer (49–3552 µg h −1 ) compared to the laser printers (5782–7735 µg h −1 ). A total of 14 VOCs were identified during 3-D printing that were not present during laser printing. 3-D printed objects continued to off-gas styrene, indicating potential for continued exposure after the print job is completed. Carbonyl reaction products were likely formed from emissions of the 3-D printer, including 4-oxopentanal. Ultrafine particles generated by the 3-D printer using ABS and a laser printer contained chromium. Consideration of the factors that influenced the release of chemical contaminants (including known and suspected asthmagens such as styrene and 4-oxopentanal) from a FDM 3-D printer should be made when designing exposure assessment and control strategies.